2019
DOI: 10.12659/msm.918364
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin Inhibits Cell Viability and Increases Apoptosis of SW620 Human Colon Adenocarcinoma Cells via the Caudal Type Homeobox-2 (CDX2)/Wnt/β-Catenin Pathway

Abstract: BackgroundCurcumin is a polyphenol compound extracted from the root of the herb Curcuma longa, which is used in traditional Chinese medicine (TCM). Worldwide, colorectal carcinoma (CRC) is an increasing cause of morbidity and mortality. This study aimed to investigate the effects of increasing concentrations of curcumin on cell viability, proliferation, and apoptosis of SW620 human colonic adenocarcinoma cells cultured in vitro, and the signaling pathways involved.Material/MethodsSW620 human colonic adenocarci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(12 citation statements)
references
References 19 publications
(25 reference statements)
1
10
0
Order By: Relevance
“…Curcumin was also reported to be a regulator of the Wnt signaling pathway. It was suggested that curcumin plays roles in regulating the Wnt pathway by affecting microRNAs, caudal type homeobox-2 (CDX2), glypican-3, and other molecular targets [29][30][31]. In the present study, we found that in H/Rexposed neurons, curcumin pre-treatment decreased Wnt5a expression, JNK1 phosphorylation, and NF-kB nuclear translocation.…”
Section: Discussionsupporting
confidence: 57%
“…Curcumin was also reported to be a regulator of the Wnt signaling pathway. It was suggested that curcumin plays roles in regulating the Wnt pathway by affecting microRNAs, caudal type homeobox-2 (CDX2), glypican-3, and other molecular targets [29][30][31]. In the present study, we found that in H/Rexposed neurons, curcumin pre-treatment decreased Wnt5a expression, JNK1 phosphorylation, and NF-kB nuclear translocation.…”
Section: Discussionsupporting
confidence: 57%
“…A previous investigation showed that curcumin suppresses gastric cancer cells through inhibiting the Wnt/β-catenin signaling pathway [ 24 ]. A recent study reported that curcumin inhibits the Wnt/β-catenin pathway by increasing CDX2 expression in CRC cells [ 15 ]. In the present investigation, non-cytotoxic concentrations of curcumin were used to treat SW480 cells to avoid cell death-related gene expression changes.…”
Section: Discussionmentioning
confidence: 99%
“…Cell viability was assessed by 3-(4,5-Dimethylthiazol-2-Yl)-2,5-Diphenyltetrazolium Bromide (MTT) assay according to the protocol described in previous studies [ 15 ]. SW480 cells, at a density of 1×10 4 cells per well, were treated with curcumin at 0, 0.1, 0.2, 0.4, 0.8, or 1.6 μmol/L for 24 h. An MTT assay kit (Beyotime, Shanghai, China) was used to carry out the assay.…”
Section: Methodsmentioning
confidence: 99%
“…Curcumin is another inhibitor of ß -catenin in many cancers ( Deguchi, 2015 ). Previous studies illustrated caudal type homeobox-2 (CDX2) is a mediator of the Wnt signaling pathway, and curcumin can reduce cell proliferation and increase apoptosis by restoring CDX2 which inhibited the Wnt/β-catenin signaling pathway ( Jiang X. et al, 2019 ). Besides, curcumin might exert anti-resistant effect of 5-FU on rHCT-116 cells by controlling WNT signal pathway to reverse the EMT progress ( Lu et al, 2020 ).…”
Section: Therapeutic Mechanism Of Active Compounds Against Crc In Situmentioning
confidence: 99%